Whole or incomplete: the myth of body perfection - Khetarpal, Abha (Research and Humanities in Medical Education, 2017)
The media’s and society’s prejudice in favor of ‘ablesim’ propagates the myth of body perfection. As a result we pursue perfection – the concept of ableism invades our minds as well as our culture and we all succumb to it’s lure. Disability is socially constructed; it is ableism that compels people to believe that perfection is normal. This belief is nothing less than social oppression. Even the rehabilitation therapies send out strong signals that persons with disabilities are ‘deficient’ and ‘abnormal’, and that to become a "valued" person they would have to overcome their disabilities. Since the physical component of self-concept is important in maintenance of health and in identity formation, such pressures can lead to a distortion of self-concept. The desire for human perfection can lead to medical conditions such as obsessive compulsive disorder, anorexia nervosa, or depression. It can also impact our understanding of what it means to be human and what signifies a perfect or happy life. This article expounds on why we must achieve, value, and polish psychological maturity through awareness, self-regulation, responsibility, interdependence, honesty and integrity.